Rethinking prestige branding : secrets of the Ueber-Brands - Schaefer, Wolfgang; Kuehlwein, J. P. (London ; Philadelphia : Kogan Page, 2015)
"What makes someone do and pay anything to clinch a Kelly bag? Why are Cirque Du Soleil or Grey Goose so successful despite breaking all the conventions of their industries? What does Gucci's approach to marketing have in common with Nespresso's?Rethinking Prestige Branding uncovers the formula for what drives the success of great luxury brands. The book offers a behind-the-scenes look into not just the practical marketing of brands, but how consumers respond to them psychologically and emotionally.With insights from interviews with 50 premium brand experts and over 100 case studies, this book will fascinate the marketing professional just as much as those who are simply curious about how premium brands tick. "--
"What makes someone covet a Kelly bag? Why are Cirque Du Soleil or Grey Goose so successful despite breaking all the conventions of their categories? What does Gucci's approach to marketing have in common with Nespresso's? And why do some people pay a relative fortune for Renova toilet paper or Aesop detergent even though they hardly ever 'advertise' and seem to have none of the 'functional performance advantages' conventional marketers would seek to demonstrate? Prestige brand experts JP Kuehlwein and Wolfgang Schaefer have dedicated themselves to studying what drives the success of prestige brands. Rethinking Prestige Branding collects their insights. Uncovering the secrets of why and how some brands are created more equal than others, Rethinking Prestige Branding includes over 100 case studies from Apple and Abercrombie & Fitch to Tate Modern and Tesla. Rather than re-telling brand success stories or re-hashing long-standing marketing principles, it takes readers on a colourful journey behind the scenes of today's marketing pros. This book will fascinate the marketing professional just as much as those who are simply curious as to how premium brands tick"--
Section - ONE: Rethinking prestige branding; Chapter - 01: The times they are a-changing; Chapter - 02: From marker to myth - a brief history of branding; Chapter - 03: A new kind of prestige - or what we mean by Ueber-BrandsT; Section - TWO: The seven secrets of Ueber-Brands; Chapter - 04: Principle 1: Mission incomparable - the first rule is to make your own; Chapter - 05: Principle 2: Longing versus belonging - the challenge is both; Chapter - 06: Principle 3: Un-selling - the superiority of seduction; Chapter - 07: Principle 4: From myth to meaning - the best way up is to go deep; Chapter - 08: Principle 5: Behold! - the product as manifestation; Chapter - 09: Principle 6: Living the dream - the bubble shall never burst; Chapter - 10: Principle 7: Growth without end - the ultimate balancing act
business bookfair2016
Includes bibliographical references and index.
Keywords: Branding (Marketing); Brand name products; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Advertising & Promotion